2008
DOI: 10.1016/j.bbamcr.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Novel translocation responses of cytosolic phospholipase A2α fluorescent proteins

Abstract: Cytosolic phospholipase A2 (cPLA2)alpha responds to the rise in cytosolic Ca2+ ([Ca2+]i) attending cell stimulation by moving to intracellular membranes, releasing arachidonic acid (AA) from these membranes, and thereby initiating the synthesis of various lipid mediators. Under some conditions, however, cPLA2alpha translocation occurs without any corresponding changes in [Ca2+]i. The signal for such responses has not been identified. Using confocal microscopy to track fluorescent proteins fused to cPLA2alpha o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 48 publications
2
27
0
1
Order By: Relevance
“…Most of the research carried out to date has thoroughly documented the translocation of cPLA 2 ␣ to intracellular membranes such as those of the nuclear envelope, Golgi complex, or endoplasmic reticulum ( 9 ). A few instances have been reported of translocation of cPLA 2 ␣ to cellular membranes different to those indicated above ( 20,35,36 ). This study adds to these studies by showing that the phagosomal membrane of human macrophages is also a site for cPLA 2 ␣ translocation during activation conditions.…”
Section: Discussionsupporting
confidence: 53%
“…Most of the research carried out to date has thoroughly documented the translocation of cPLA 2 ␣ to intracellular membranes such as those of the nuclear envelope, Golgi complex, or endoplasmic reticulum ( 9 ). A few instances have been reported of translocation of cPLA 2 ␣ to cellular membranes different to those indicated above ( 20,35,36 ). This study adds to these studies by showing that the phagosomal membrane of human macrophages is also a site for cPLA 2 ␣ translocation during activation conditions.…”
Section: Discussionsupporting
confidence: 53%
“…Likewise, cells depleted of cPLA 2 ␣ by RNA silencing result in the appearance of tubulo-vesicular profi les of the smooth endoplasmic reticulum, compatible with a role of cPLA 2 ␣ in regulating the structure of this organelle (11). cPLA 2 ␣ has recently been reported to translocate to LD after cell activation (24,25,63). Studies on cPLA 2 ␣ targeting to membranes have indicated that, in addition to increased Ca 2+ availability, there are other factors regulating the association of the enzyme to membranes, including the local concentration of phosphoinositides in the membrane (64,65) and the phosphorylation state of the cPLA 2 ␣ (66).…”
Section: Discussionmentioning
confidence: 80%
“…(10,(20)(21)(22). Decided amounts of arachidonic acid (AA) are present in the phospholipid monolayer surrounding the LD, and a variety of enzymes involved in AA metabolism have been demonstrated to localize in LDs (23)(24)(25)(26). One of these enzymes is the group IVA phospholipase A 2 , also known as cytosolic phospholipase A 2 ␣ (cPLA 2 ␣ ), a central enzyme for the release of AA from phospholipids (27)(28)(29)(30)(31).…”
Section: Measurement Of Fatty Acid Incorporation Into Tagmentioning
confidence: 99%
“…AA esterified in phospholipids, and some AA-metabolizing enzymes have been localized in part to LDs, including cyclooxygenase-2, 5-and 15-lipoxygenases, and PGE 2 synthase (29). Very recently, translocation of cPLA 2 a to LDs has also been shown (35,69). This work describes lipin-1a as another lipid signaling enzyme associated to LD membranes.…”
Section: Discussionmentioning
confidence: 92%